Defective repair of O6-methylguanine-DNA in primary Sjögren's syndrome patients predisposed to lymphoma. Issue 3 (March 1995) - Guo, K; Major, G; Foster, H; Bassendine, M; Collier, J; Ross, D; Griffiths, I
Abstract : OBJECTIVE--To investigate a role for mutation in the aetiogenesis of autoimmune disease by examining levels of repairing enzyme for the promutagenic DNA base lesion, O6-methylguanine, in lymphocyte extracts from patients with autoimmune diseases. We included primary Sjögrens syndrome (PSS) patients because of the additional relevance of their being at increased risk (> 40-fold) of developing lymphoma. METHODS--Lymphocytes were prepared from patients with PSS (n = 22) (12 with parotid gland enlargement, an indicator of extensive lymphoproliferation), rheumatoid arthritis (n = 12), primary biliary cirrhosis (n = 11), osteoarthritis (n = 12), and healthy individuals (n = 11). MGMT amounts were determined in lymphocyte extracts by direct enzyme assay and expressed in relation to total extract DNA, protein, or cell number. RESULTS--We found no defect in the repairing methyltransferase enzyme between any of the groups, except in PSS patients at increased risk of developing lymphoma (those with enlarged parotid glands): p < 0.0001 and p = 0.0056, compared with healthy controls and PSS patients without parotid gland swelling, respectively. CONCLUSIONS--Our findings implicate persistence of O6-methylguanine-DNA in the aetiology of lymphoma associated with PSS, and raise the possibility that an alternative repair process for O6-methylguanine-DNA, nucleotide excision repair, might be defective in autoimmune disease.